2019
DOI: 10.17826/cumj.463589
|View full text |Cite
|
Sign up to set email alerts
|

Tip 2 diyabet hastalarında anksiyete ve depresyon riski ve ilişkili faktörler

Abstract: Öz Purpose: In our study, we aimed to determine the anxiety and depression risks of patients with type 2 diabetes who have an important public health problem in the world and in Turkey and to determine the conditions related to these risks. Materials and Methods: This cross-sectional analytical study was performed in 636 patients with type 2 diabetes who presented to the Internal Diseases Clinic. A questionnaire form prepared by the researchers was used for sociodemographic data. The Hospital Anxiety and Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
0
0
2
Order By: Relevance
“…Diabetes is among the important chronic diseases that increase the risk of depression. [30][31][32][33] In previous studies, similar to our study, depression scores of patients with T2D were significantly higher. [27,29,31] In addition, in the study by Mumtaz et al [7] comparing the risk of depression in patients with T1D and T2D, 20% of patients with T1D and 40.6% of patients with T2D showed a risk of depression.…”
Section: Tablesupporting
confidence: 86%
See 2 more Smart Citations
“…Diabetes is among the important chronic diseases that increase the risk of depression. [30][31][32][33] In previous studies, similar to our study, depression scores of patients with T2D were significantly higher. [27,29,31] In addition, in the study by Mumtaz et al [7] comparing the risk of depression in patients with T1D and T2D, 20% of patients with T1D and 40.6% of patients with T2D showed a risk of depression.…”
Section: Tablesupporting
confidence: 86%
“…This process may have negatively affected their adaptation to the disease and increased their depression scores. [29][30][31] In addition, it was reported that the type of treatment (Insulin was superior to oral diabetics.) received by women with T2D increased the risk of depression because it affected insulin regulation.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Öte yandan ikinci bir anlayışa göre ise, kadınların fuhuş nedeniyle maruz kaldıkları şiddet, sömürü ve diğer hak ihlallerinin, aslında toplumsal yaşamın ve profesyonel 141 Göçmen, s. 23. iş yaşamının diğer noktalarından çok da farklı olmadığı da belirtilmektedir 146 . Buna göre, para karşılığında cinsel ilişkiye girilmesi, bir iş kolu olarak tanımlanmalı ve hukuken düzenlenmelidir 147 .…”
Section: A İnsan Ticareti Suçu Ve Fuhuş İlişkisiunclassified
“…Sekson cinsi köpeklerin bakım ve idaresiyle ilgilenen askere seksoncu, seksoncuların başındaki kişiye ise seksoncubaşı denilmektedir 47 . Yetmiş birinci ortanın bakımını yürüttükleri seksonlar bilhassa ayı avında kullanılmaktaydı 48 .…”
Section: Seksoncu Ortasının Vazifeleriunclassified